ETG-Fb. 161: CIPS 2020 : 11th International Conference on Integrated Power Electronics Systems, Proceedings March, 24 - 26, 2020, Berlin, Germany. - VDE ETG; VDE ETG (ETG-Fachberichte, 2020)
Long description: In the next decades, power electronic system development will be driven by energy saving systems, intelligent energy management, power quality, system miniaturization and high reliability. Monolithic and hybrid system integration will include advanced device concepts including wide bandgap devices, new packaging technologies and the overall integration of actuators/drives (mechatronic integration). CIPS is consequently focused on the following main aspects: - assembly and interconnect technology for power electronic devices and converters - integration of hybrid systems and mechatronic systems with high power density - systems and components operational behaviour and reliability Basic technologies for integrated power electronic systems as well as upcoming new im-portant applications will be presented in interdisciplinary invited papers. In 2020 the successful story of CIPS will continue as the conference focus is today more important than ever - increasing functionality, energy efficiency and system reliability while decreasing cost. We are pleased to welcome all engineers coming from industry and academia engaged in power electronics-related - system development - component development - reliability engineering - research.